NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL DAUN YANG JATUH TAK PERNAH MEMBENCI ANGIN KARYA TERE LIYE - Angela, Dita; Thahar, Harris Effendi (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT  The purpose of this study is to describe the velues of character education in Tere Liye’s novel Daun yang Jatuh Tak Pernah Membenci Angin. The type of this study is qualitative research with descriptive method and using triangulation technique to validate the data. The research data is in the form of words, phrases, sentences, and discourses that show the actions of the characters, the words of the characters and the narrator, which indicate the values of character education found in Tere Liye's novel Daun yang Jatuh Tak Pernah Membenci Angin. The data collection technique of this study is to read and understand Tere Liye's novel Daun yang Jatuh Tak Pernah Membenci Angin then recording the data related to character education values in Tere Liye's novel Daun yang Jatuh Tak Pernah Membenci Angin in the form of units of events from character’s behavior. The data analysis technique of this research is describing the values of character education in Tere Liye's novel Daun yang Jatuh Tak Pernah Membenci Angin which is seen in a unit of character events, classifying, analyzing data, interpreting, and compiling reports.As the results of the research founded 72 values of character education, namely 5 values of religious character education, 17 values of hard work character education, 4 values of independent character education, 6 values of curiosity character education, 5 values of education value achievement, 9 values of friendly character education, 3 values of character education are fond of reading, 15 values of moral value character education, and 8 values of education responsibility. The most dominant valueof character education in Tere Liye's novel Daun yang Jatuh ismoral value character education as much as 15 data. Kata kunci: Nilai, Pendidikan Karakter, Novel Daun yang Jatuh Tak Pernah Membenci Angin